Effects of reducing and postponing controlled-release urea application on soil nitrogen regulation and maize grain yield - Ji, Pengtao; Peng, Yujuan; Cui, Yongwei; Li, Xiangling; Tao, Peijun; Zhang, Yuechen (International Journal of Agricultural and Biological Engineering, 2022)
Controlled-release urea (CRU-N) fertilizer application is a solution to improve the utilization rate of nitrogen (N), reduce economic costs and improve crop yields. It is significant to study the effects of release CRU-N reduction and the combined application of conventional urea on soil N control and the large-scale maize planting system. In this study, the effects of controlled-release nitrogen fertilizer reduction and postponement on soil nitrogen components, enzyme activities, and yields were investigated. Seven treatments were set up in this study, including no N fertilizer (CK), 100% conventional urea (U), 100% controlled-release urea (S), 30% controlled-release urea (SU3/7), 50% controlled-release urea (SU5/5), 70% controlled-release urea (SU7/3) and Sodium Salt of Polyaspartic Acid (PASP)-N. The results showed that mixed CRU-N and urea increased yields and net benefits compared with conventional urea at the same application rate of N, and reduced N loss. The application of CRU-N at 70% for maize represented the best overall effects. Compared with U treatment, soil ammonium nitrogen (NH4-N), soil nitrate-nitrogen (NO3-N), and microbial biomass nitrogen (SMB-N) of CRU-N at 70% (SU7/3) increased by 35.00%, 15.53%, and 25.04%. However, soil nitrate reductase (S-NR) and urease (S-UA) were the best in SU5/5 and significantly higher than other treatments. The applications of CRU-N would effectively increase soil N; CRU-N in 50% proportion can promote the maize root growth and improve the efficient utilization of N by soil microorganisms. Like the yields (9186.61 kg/hm2), expertly in the proportion of 70% CRU-N (SU7/3) plays a vital role in a wheat-maize rotation system, which can potentially be used to improve the yields, nitrogen use efficiency, and net benefit with low N losses. In conclusion, using CRU-N fertilize effectively improves soil nitrogen, and various ratios of CRU-N can ensure the continuous release the nutrients during the growing period. And among the different proportions of CRU-N, it is optimal in SU7/3.Keywords: controlled-release urea, nitrogen regulation, maize grain yield, soil, reducing, postponingDOI: 10.25165/j.ijabe.20221501.6888Citation: Ji P T, Peng Y J, Cui Y W, Li X L, Tao P J, Zhang Y C. Effects of reducing and postponing controlled-release urea application on soil nitrogen regulation and maize grain yield. Int J Agric & Biol Eng, 2022; 15(1): 116–123.